Quality of Life in Patients with Neurodegenerative Diseases - Batista, Patricia (2018)
Neurodegenerative diseases are characterized by a progressive deterioration of brain function, with a significantly consequent decrease in the quality of life of patients and their families. Due to increasing life expectancy, the incidence of these diseases has increased over the years, and has been under research. Objective: The aim of this paper is to systematically review the scientific literature about the evaluation of life’ quality in patients with neurodegenerative diseases. Methods: Reflective systematic literature review on Pubmed, MedLine and Scopus database with the keywords "quality of life of Patients" and "neurodegenerative diseases" was analyzed. It was analyzed in the period between 2000 and 2015. PRISMA criteria reporting of systematic reviews and meta-analyses were applied. The inclusion criteria were: usage of instrument to measure life’ quality, presenting quantitative or qualitative results, and psychometric studies. It was excluded articles reviews outside the scope of the subject, theoretical articles and new therapies, diagnostic and palliative care.Results: After applying the methodology, five scientific articles were included in the study. The measuring instruments were used the dimensions (physical, mental, social and environmental) were analyzed. It was analyzed the results obtained in the studies. Conclusions: This literature review indicated that more research is needed to assess the impact of quality of life in patients with degenerative pathologies. The implications of these findings and potential directions for future research are discussed.